67 Effects of Long-term Valbenazine on Psychiatric Status in Patients with Tardive Dyskinesia and a Primary Mood Disorder. (12th March 2019) - McIntyre, Roger S.; Remington, Gary; Correll, Christoph U.; Weber, Rachel; Farahmand, Khodayar; Lundt, Leslie; Burke, Joshua; Siegert, Scott
Abstract: Objective: Valbenazine is approved for tardive dyskinesia (TD) in adults based on clinical trials that included patients with mood disorders (e.g., bipolar disorder, major depressive disorder). In two long-termphase 3 trials, KINECT 3 (NCT02274558) and KINECT 4 (NCT02405091), sustained TD improvements were found in participants who received once-daily treatment with valbenazine (40 or 80mg). Data from these studies were analyzed post hoc to evaluate changes in psychiatric status of patients with a primary mood disorder. Methods: Data were pooled from participants with mood disorders in KINECT 3 (6-week double-blind, placebo-controlled period; 42-week double-blind extension period; 4-week drug-free washout) and KINECT 4 (48week open-label treatment; 4-week drug-free washout). At screening, patients must have had a Brief Psychiatric Rating Scale total score <50. Mood changes were evaluated after long-term treatment (Week 48) and washout (Week 52) using the Young Mania Rating Scale (YMRS) and Montgomery-Åsberg Depression Rating Scale (MADRS). For each scale, mean changes from baseline in the total score and individual item scores were analyzed descriptively. Results: Of the 95 participants with a primary mood disorder (40mg, n=32; 80mg, n=63), 59 (62.1%) were diagnosed with bipolar disorder, 32 (33.7%) with major depressive disorder, and 4 (4.2%) with another mood disorder. A majority of all mood participants received concomitant antidepressants (84.2%) and/or antipsychotics (76.8%) during treatment; other common concomitant medications included antiepileptics (47.4%), anxiolytics (38.9%), and anticholinergics (22.1%). Mean YMRS and MADRS total scores in all mood participants indicated mood symptom stability at baseline (YMRS, 2.7; MADRS, 5.9). This stability was maintained during the studies, as indicated by minimal changes from baseline in mean total scores (YMRS: Week 48, 1.0; Week 52, –1.0; MADRS: Week 48, 0.3; Week52, 0.9). Changes in individual items on both scales were also small (<±0.3), indicating no clinically significant changes or worsening in specific mood symptoms or domains. Conclusions: Mood symptom stability was maintained in patients with TD and a primary mood disorder who received up to 48 weeks of treatment with once-daily valbenazine in addition to their psychiatric medication(s). Funding Acknowledgements: Neurocrine Biosciences, Inc.